The Presumption for Detention Statute's Relationship to Release Rates. - Austin, Amaryllis (Federal Probation, 2017)
The article discusses relationship between the presence of the presumption and release rates. Topics discussed include presumption on the release recommendations made by pretrial services officers, passage of the Bail Reform Act of 1966 and concern over judicial officers' lack of discretion to consider a defendant's dangerousness.